Prevention of mammary tumor progression by silencing HoxA1 via intraductal injection of nanoparticle-formulated siRNA - Brock, Amy (Sci Transl Med, 2014)
With advances in screening, the incidence of detection of premalignant breast lesions has increased in recent decades; however, treatment options remain limited to surveillance or surgical removal by lumpectomy or mastectomy. We hypothesized that disease progression could be blocked by RNA interference (RNAi) therapy and set out to develop a targeted therapeutic delivery strategy. Using computational gene network modeling, we identified HoxA1 as a putative driver of early mammary cancer progression in transgenic C3(1)-SV40TAg mice. Silencing this gene in cultured mouse or human mammary tumor spheroids resulted in increased acinar lumen formation, reduced tumor cell proliferation, and restoration of normal epithelial polarization. When the HoxA1 gene was silenced in vivo via intraductal delivery of nanoparticle-formulated small interfering RNA (siRNA) through the nipple of transgenic mice with early-stage disease, mammary epithelial cell proliferate rates were suppressed, loss of estrogen and progesterone receptor expression was prevented, and tumor incidence was reduced by 75%. This approach that leverages new advances in systems biology and nanotechnology offers a novel non-invasive strategy to block breast cancer progression through targeted silencing of critical genes directly within the mammary epithelium.